Polyanhydride nanoparticles stabilize pancreatic cancer antigen MUC4β - Liu, Luman (J Biomed Mater Res A, 2020)
Pancreatic cancer (PC) is one of the most lethal malignancies and represents an increasing and challenging threat, especially with an aging population. The identification of immunogenic PC-specific upregulated antigens and an enhanced understanding of the immunosuppressive tumor microenvironment have provided opportunities to enable the immune system to recognize cancer cells. Due to its differential upregulation and functional role in PC, the transmembrane mucin MUC4 is an attractive target for immunotherapy. In the current study we characterized the antigen stability, antigenicity and release kinetics of a MUC4β-nanovaccine to guide further optimization and, in vivo evaluation. Amphiphilic polyanhydride copolymers based on 20 mol % 1,8-bis(p-carboxyphenoxy)-3,6-dioxaoctane and 80 mol % 1,6-bis(p-carboxyphenoxy)hexane were used to synthesize nanoparticles. Structurally stable MUC4β protein was released from the particles in a sustained manner and characterized by gel electrophoresis and fluorescence spectroscopy. Modest levels of protein degradation were observed upon release. The released protein was also analyzed by MUC4β-specific monoclonal antibodies using ELISA and showed no significant loss of epitope availability. Further, mice immunized with multiple formulations of combination vaccines containing MUC4β-loaded nanoparticles generated MUC4β-specific antibody responses. These results indicate that polyanhydride nanoparticles are viable MUC4β vaccine carriers, laying the foundation for evaluation of this platform for PC immunotherapy.